Detection and localization of LysA and GP1 proteins of the mycobacteriophage Ms6 - Silva, Alessa Ede Valverde da, 1987- (2012)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2011